A study on the implementation of safety practices in Malaysia construction industry - Lau, Zi Thiam (2014)
Construction industry is one of the industries which has the highest accident rate in Malaysia. Most of the cases happened in construction industry indicate that the industry condition is serious. As a result, implementation of safety practices is needed to improve the current unsafe condition of the construction site which causes an accident and death annually. This study mainly focuses on the implementation level of the safety practices by the construction personnels and its challenges faced during its implementation. The survey through questionnaires and interviews are conducted to obtain all the required information. The questionnaires are distributed through email in West Malaysia while the interviews only involved 10 construction companies in the areas of Penang and Kedah. Based on the result of analysis, it showed that the four safety practices are highly implemented by the majority. Eighty six percent of the respondents implemented that understand of every work activity by the supervisor or site worker in encouraging the safety in designing construction process. Eighty two percent of the respondents has consultation of organization's safety work in site. Seventy eight percent of the respondents identify and improve the weakness of construction safety. Seventy seven percent of the respondents established the planning of construction safety. This allows the construction workers to concern about their responsibility and gain new experience toward their responsibility in ensuring the construction safety. However, the challenge which faced by the majority construction professionals in implementing these safety practices is the tight project schedule in construction project. In order to fasten the construction project, some of the safety steps are skipped or ignored. When the safety steps are ignored, the death and injury are occurred consequently. Besides, lack of safety awareness among the construction workers in their construction project and employers' unwillingness to pay for safety aspects are the challenges faced by the respondents in implementing the safety practices. Hence, several recommendations are provided to improve the current safety practices and the challenges. Enforcement and increasing the current safety training program are required to be conducted by the government and employer as well.